Geomorphological mapping of the Vacacaí river hydrographic basin (BHRV): Geomorphology as a subsidy to the knowledge of the physical environment - Schnorr, Giorge Gabriel; Sccoti, Anderson Augusto Volpato (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Relief and its dynamics are understood as complex and the result of numerous exogenous and endogenous relationships. Geomorphological mapping emerges as an important tool for characterization and interpretation of geomorphological characteristics. The present work aims to present a geomorphological characterization of the Vacacaí River Hydrographic Basin (BHRV) based on different scales of analysis and cartographic products. The geomorphological classification presented here is based on the methodology proposed by Ross (1992), with adaptations and automation of the definition of cartographic products, thus defining 4 levels of analysis. In terms of results, there is a predominance of sedimentary structures from the Peripheral Depression, morpho sculptures from the Jacuí River Depression, patterns of smooth hills over sedimentary and elements from flat áreas. The methodology proved to be efficient and brought important aspects of relief and cartographic products that can serve for spatial organization actions.